A função social da empresa e a tutela dos interesses difusos e coletivos - Vaughn Neto, Melford (2023)
The scope of the present work is the descriptive and analytical study of the social function of the company as an instrument for the regulation of general and collective interests, as a consequence of the profound transformations in human society in all its spheres - social, economic, political, legal - from which originated the contemporary social body and, especially, the modern company. The general objective is, therefore, the analysis of the social function of the company as a means capable of protecting the general and collective interests, stemming from an examination of possible articulations between law, market and the principle of social solidarity and that, consequently, encompasses the business phenomenon (historical-dogmatic construction) and the social function of the company (understanding, delimitation, interrelationship and instrumentalization). The objective is to face the historical components of the Rule of Law and its relationship with the economy, as well as, to present the contemporary perspective of the corporate phenomenon and its relationship with the collectivity - in light of the legal dogmatics. We face, thus, the construction of the principle of the social function of the company, placing it, consequently, as an instrument at the service of the general and collective rights, as well as, we seek to respond for its hermeneutic-integrative dimension in collective processes